Evaluation of commonly used cardiovascular drugs in inhibiting vonoprazan metabolism in vitro and in vivo - Wang, Yiran; Shi, Jihua; Dai, Dapeng; Cai, Jianping; Wang, Shuanghu; Hong, Yun; Zhou, Shan; Zhao, Fangling; Zhou, Quan; Geng, Peiwu; Zhou, Yunfang; Xu, Xue; et al. (Frontiers in Pharmacology, 2022)
As a novel acid-suppressing drug, vonoprazan shows the potential to substitute traditional proton-pump inhibitors. With the spread use of it, some adverse effects have emerged due to drug-drug interactions, needing further studies to assist to avoid them. Our study is the first experiment that evaluated the drug-drug interactions of eleven common cardiovascular drugs that inhibit vonoprazan metabolism in vitro and in vivo. Rat liver microsome incubation and molecular simulation docking were applied to explore the inhibition mechanism. Amlodipine and nifedipine showed inhibitory effects on vonoprazan metabolism both in rat liver microsome and human liver microsome in the first evaluation part in vitro. The inhibition mechanism analysis results demonstrated that amlodipine and nifedipine might inhibit the metabolism of vonoprazan by a mixed type of competitive and non-competitive inhibition. However, the pharmacokinetic data of the vonoprazan prototype revealed that amlodipine affected vonoprazan in vivo, while nifedipine did not. Thus, amlodipine should be paid more attention to when prescribed with vonoprazan. Furthermore, the changes in its carboxylic acid metabolites MI hinted at a complex situation. Molecular simulation suggested the CYP2B6 enzyme may attribute more to this than CYP3A4 and further inhibitory experiments preliminarily verified this speculation. In conclusion, the combination of cardiovascular drugs should be paid particular attention to in clinical prescriptions, especially that of amlodipine.